Neogenesis of lymphoid structures and antibody responses occur in human melanoma metastases - Cipponi, Arcadi; Mercier, Marjorie; Seremet, Teofila; Baurain, Jean-François; Théate, Ivan; van den Oord, Joost; Stas, Marguerite; Boon, Thierry; Coulie, Pierre G; van Baren, Nicolas (Cancer research (Chicago, Ill.), 2012)
Lymphoid neogenesis, or the development of lymphoid structures in nonlymphoid organs, is frequently observed in chronically inflamed tissues, during the course of autoimmune, infectious, and chronic graft rejection diseases, in which a sustained lymphocyte activation occurs in the presence of persistent antigenic stimuli. The presence of such ectopic lymphoid structures has also been reported in primary lung, breast, and germline cancers, but not yet in melanoma. In this study, we observed ectopic lymphoid structures, defined as lymphoid follicles comprising clusters of B lymphocytes and follicular dendritic cells (DC), associated with high endothelial venules (HEV) and clusters of T cells and mature DCs, in 7 of 29 cutaneous metastases from melanoma patients. Some follicles contained germinal centers. In contrast to metastatic lesions, primary melanomas did not host follicles, but many contained HEVs, suggesting an incomplete lymphoid neogenesis. Analysis of the repertoire of rearranged immunoglobulin genes in the B cells of microdissected follicles revealed clonal amplification, somatic mutation and isotype switching, indicating a local antigen-driven B-cell response. Surprisingly, IgA responses were observed despite the nonmucosal location of the follicles. Taken together, our findings show the existence of lymphoid neogenesis in melanoma and suggest that the presence of functional ectopic lymphoid structures in direct contact with the tumor makes the local development of antimelanoma B- and T-cell responses possible.